1989
DOI: 10.1007/bf00665448
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation kinetics of chromium and morphological phenomena

Abstract: P02 show good sulphidation resistance due to the higher chromia content in the oxide scale. Yttrium-ion implantation of Incoloy 800H has also a beneficial effect on sulphidation, if preoxidation is applied. The reason for this is presumably the segregation of yttrium to grain boundaries of the oxide. Furthermore, the oxidation kinetics of Incoloy 800H are independent of the partial pressure of the oxygen. Mechanical testing of the preformed oxide scale/substrate combinations in air at 600~ by means of constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…As Fig. shows, only alloys SG1 and SG2 show the typical wrinkling , which does not appear in alloys S15 and SG12.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…As Fig. shows, only alloys SG1 and SG2 show the typical wrinkling , which does not appear in alloys S15 and SG12.…”
Section: Resultsmentioning
confidence: 84%
“…Scale wrinkling is a common feature that occurs in chromia scales and is attributed to the lateral growth of chromia within the scale . This feature is the result of a stress‐releasing process via plastic deformation of the scale at high temperature .…”
Section: Resultsmentioning
confidence: 99%
“…23,24 In explaining experimental observations, some authors 19,23,24 assumed that classical defect equilibria related to an oxide lattice are applicable for describing transport processes along grain boundaries. Although it has not yet unequivocally been demonstrated that this is indeed the case, this assumption is also followed in the present considerations.…”
Section: Effect Of H-defects On Concentration Of Intrinsic Native Dementioning
confidence: 99%
“…31 A major problem in interpreting the results on the basis of point defects is that chromia growth is claimed to be dominated by grain boundary rather than lattice transport. 3,23 In explaining experimental observations, some authors 3,23,26 assumed that classical defect equilibria related to an oxide lattice are applicable for describing transport processes along grain boundaries, however, it has not yet unequivocally been demonstrated that this is indeed the case.…”
Section: Single Stage Exposuresmentioning
confidence: 99%
“…This may occur as a result of different types and/or concentrations of point defects in the two sublayers and/or due to large differences in densities of grain boundaries which will affect the overall ion transport as grain boundaries are known to be preferred diffusion paths in chromia scales at the prevailing temperature. 3,23 The formation of voids will reduce the area available for diffusion of the mobile species in the scale and will thus result in a decrease of the scale growth rate. This may be the explanation for the observed decrease in the weight gain rate in the thermogravimetric studies after switching the gas from the dry to the wet gas (Fig.…”
Section: Two-stage Oxidationmentioning
confidence: 99%